Acute kidney injury in HIV-infected children: comparison of patients according to the use of highly active antiretroviral therapy - Douglas de Sousa Soares; Malena Gadelha Cavalcante; Samille Maria Vasconcelos Ribeiro; Rayana Café Leitão; Ana Patrícia Freitas Vieira; Roberto da Justa Pires Neto; Geraldo Bezerra da Silva Junior; Elizabeth de Francesco Daher (Elsevier, 2016)
Objective: To assess clinical and laboratory data, and acute kidney injury (AKI) in HIV-infected children using and not using highly active antiretroviral therapy (HAART) prior to admission. Methods: A retrospective study was conducted with HIV-infected pediatric patients (<16 years). Children who were using and not using HAART prior to admission were compared. Results: Sixty-three patients were included. Mean age was 5.3 ± 4.27 years; 55.6% were females. AKI was observed in 33 (52.3%) children. Patients on HAART presented lower levels of potassium (3.9 ± 0.8 vs. 4.5 ± 0.7 mEq/L, p = 0.019) and bicarbonate (19.1 ± 4.9 vs. 23.5 ± 2.2 mEq/L, p = 0.013) and had a higher estimated glomerular filtration rate (102.2 ± 36.7 vs. 77.0 ± 32.8 mL/min/1.73 m2, p = 0.011) than those not on HAART. In the multivariate analysis, the use of HAART prior to the admission was a protective factor for AKI (p = 0.036; OR = 0.30; 95% CI = 0.097-0.926). Conclusion: AKI is a common complication of pediatric HIV infection. Use of HAART prior to the admission preserved glomerular filtration and was a protective factor for AKI, but increased medication side effects, such as hypokalemia and renal metabolic acidosis. Resumo: Objetivo: Avaliar dados clínicos e laboratoriais, bem como ocorrência de lesão renal aguda (LRA) em crianças HIV positivas com e sem uso de terapia antirretroviral altamente ativa (TARV) antes da admissão. Método: Foi realizado estudo retrospectivo em pacientes pediátricos HIV positivos (<16 anos). Foram comparadas as crianças que estavam em uso com aquelas sem uso de TARV prévia à internação. Resultados: Foram incluídos 63 pacientes, com média de idade de 5,3 ± 4,27 anos, sendo 55,6% do sexo feminino. LRA foi encontrada em 33 casos (52,3%). Os pacientes usando TARV apresentaram menores níveis de potássio (3,9 ± 0,8 vs. 4,5 ± 0,7 mEq/L, p = 0,019) e bicarbonato (19,1 ± 4,9 vs. 23,5 ± 2,2 mEq/L, p = 0,013), bem como maior taxa de filtração glomerular estimada (102,2 ± 36,7 vs. 77,0 ± 32,8 mL/min/1,73m2, p = 0,011) que o pacientes sem TARV prévia. Na análise multivariada o uso de TARV prévia à internação foi fator protetor contra LRA (p = 0,036; RC = 0,30; IC de 95% = 0,097-0,926). Conclusão: A LRA é uma complicação comum da infecção pediátrica pelo HIV. O uso de TARV antes da internação foi associado a melhor taxa de filtração glomerular e foi fator de proteção contra LRA, porém desencadeou efeitos colaterais como hipocalemia e acidose metabólica. Keywords: Acute kidney injury, HIV, Children, HAART, Palavras-chave: Insuficiência renal aguda, HIV, Crianças, TARV